The Transcription Factor Sp8 Is Required for the Production of Parvalbumin-Expressing Interneurons in the Olfactory Bulb - Li, Xiaosu (Society for Neuroscience, 2011)
Interneurons in the olfactory bulb (OB) represent a heterogeneous population, which are first produced at embryonic stages and persisting into adulthood. Using the BrdU birthdating method combined with immunostaining for several different neuronal markers, we provide the integrated temporal patterns of distinct mouse OB interneuron production from embryonic day 14 to postnatal day 365. We show that although the majority of OB interneuron subtypes continue to be generated throughout life, most subtypes show a similar “bell-like” temporal production pattern with a peak around birth. Tyrosine hydroxylase and calretinin-expressing interneurons are produced at a relatively low rate in the adult OB, while parvalbumin-expressing (PV+) interneuron production is confined to later embryonic and early postnatal stages. We also show that Dlx5/6-expressing progenitors contribute to PV+ interneurons in the OB. Interestingly, all PV+ interneurons in the external plexiform layer (EPL) express the transcription factor Sp8. Genetic ablation of Sp8 by cre/loxP-based recombination severely reduces the number of PV+ interneurons in the EPL of the OB. Our results suggest that Sp8 is required for the normal production of PV+ interneurons in the EPL of the OB. These data expand our understanding of the temporal and molecular regulation of OB interneuron neurogenesis.